The moderating effect of trait anxiety on anxiety-related thoughts and actions whilst driving. (1st December 2018) - Barnard, M.P.; Chapman, P.
Abstract: Whilst there is evidence for the impact of driving anxiety on behaviour, less exists for the impact of trait anxiety and what does exist is inconclusive. The current study explored the possibility that trait anxiety interacts with driving anxiety to impact the frequency of negative on-road thoughts and behaviours. An online survey was administered to drivers, and the State-Trait Inventory for Cognitive and Somatic Anxiety, the Driving Cognitions Questionnaire, and the Driving Behaviour Survey, were completed. Moderation analyses suggested that in addition to an increase in social concerns and aggressive responses, high trait anxiety reduced positive associations between driving anxiety and exaggerated safety-cautious behaviours, as well as the general use of maladaptive reactions to stressful situations. As scores on these subscales were still higher regardless of the reduced associations, it is argued that both drivers with a generally anxious personality and those with high levels of driving-specific anxiety should be made aware of their potential to violate traffic norms in stressful situations. Highlights: Anxious driving thoughts and behaviours were measured in an online survey. Driving anxiety significantly predicted these self-report measures. Trait anxiety moderated relationships between driving anxiety and ESCB scores. Those with high trait anxiety adopt similar actions to those with driving anxiety.